Governance analysis of MPAs in the Belgian part of the North Sea. (September 2016) - Pecceu, Ellen; Hostens, Kris; Maes, Frank
Abstract: The Belgian MPA designation process started in 1999, a journey that was characterized by several conflicts related to the multi-level government system in Belgium and obstacles, e.g. the de-designation of the Special Area of Conservation (SAC) 'Vlakte van de Raan' in 2008. On the other hand a number of successful events could be noted as well, e.g. the designation of three Special Protection Areas (SPAs) in 2005 in front of the three marine harbors, and the extension of the SAC 'Trapegeer-Stroombank' (designated in 2005) to an area >30% of the BPNS surface in 2012 (now renamed to SAC 'Vlaamse Banken'). The most important aspects that contributed to the successful designation of these MPAs in the BPNS were (1) the appointment of a minister of the North Sea in 2003 (and 2011), who was dedicated and specifically mandated to coordinate all federal North Sea matters (thus excluding fisheries); (2) the growing awareness of the need for nature conservation through different EU Directives (e.g. Marine Strategy Framework Directive (MSFD)); and (3) the level of stakeholder and public involvement, especially focusing on transparency throughout the process. Highlights: Focus on governance and related issues in the Belgian MPA designation process. Designation of MPAs closely linked to the marine spatial planning process. Strong political will and leadership essential for the successful designation. Clear evolution in the degree of stakeholder and public involvement. Document analysis, independent observations and semi-structured interviews.